Coupled nature of evening-time ionospheric electrodynamics - Joshi, L.M.; Tsai, L.C. (My University, 2018)
The F region evening electrodynamics in the equatorial region is characterized by a pre-reversal enhancement (PRE) in the zonal eastward electric field. Although the theoretical mechanisms for PRE are known, its variability, particularly day-to-day variability is not fully resolved. PRE is a large scale phenomenon driven by the F region dynamo after the sunset hours. This paper investigates whether the variability of the E region conductivity (particularly the one associated with the sporadic E, Es) has any influence on the F region dynamo and hence on the PRE of zonal electric field. Interestingly, ionosonde observations have indicated a higher occurrence of the blanketing type Es (Esb) over the low latitude on days with highly suppressed PRE of zonal electric field in comparison with the days with significantly larger PRE. Observational evidences presented in this paper suggests that the formation of the Esb in the evening hours is a sovereign process, not always controlled by the sheared F region vertical electric field of equatorial origin, mapping along the magnetic field line on to the low latitude E region. Model computations of the PRE suppression based on the measured Es densities have further substantiated the observational findings presented in this paper. These results clearly indicate that the low latitude Es has the potential to suppress the PRE of zonal electric field and possibly can play a vital role in explaining the PRE variability, particularly the day-to-day variability. Results have been discussed in light of earlier reports on PRE mechanisms and E-F region coupling processes.
Keywords: Ionospheric electrodynamics; F region dynamo; Pre-reversal enhancement; Sporadic E